Analysis of the Influence of Nozzle Structure and Hydraulic Parameters on the Cutting Efficiency of High-pressure Abrasive Water Jet (AWJ) - X. Zhu; Z. Luo; Y. Luo; C. Shi; L. Wang (Journal of Applied Fluid Mechanics)
The purpose of this study is to enhance the cutting efficiency of high-pressure abrasive water jet (AWJ) by optimizing nozzle structure and jet hydraulic parameters. To achieve nozzle structure optimization, CFD models of various nozzle shapes were established. The results indicate that the conduit length of conical nozzles has minimal impact on the cutting ability of the jet, while the conical nozzle with a taper angle of 40° exhibits excellent guiding characteristics. Furthermore, an infinite SPH AWJ cutting model with different hydraulic parameter settings was developed for the coupled numerical analysis of pump pressure, flow rate, and nozzle diameter. Through extensive numerical simulations, the study plotted curves of cutting depth and volume against pump pressure, flow rate, abrasive concentration, and nozzle diameter. The results show that, under specific hydraulic parameters, there exists an optimal abrasive concentration; and increasing the displacement leads to an increase in this optimal concentration. Furthermore, under constant pump pressure, increasing the nozzle diameter leads to an increase in flow rate. Additionally, both cutting depth and volume initially increase and then decrease, reaching their maximum values when the nozzle diameter ranges from 4mm to 5mm. The research findings provide a solid theoretical basis for abrasive jet cutting technology.